2022
DOI: 10.3390/f13050779
|View full text |Cite
|
Sign up to set email alerts
|

Extractives of Tree Biomass of Scots Pine (Pinus sylvestris L.) for Biorefining in Four Climatic Regions in Finland—Lipophilic Compounds, Stilbenes, and Lignans

Abstract: The aim of the study was to quantify total extractive contents and lipophilic compounds, stilbenes, and lignans in Scots pine stem wood, stem bark, branch biomass, and sawmill residues in four climatic regions of Finland to evaluate the most optimal sources of extractives for bio-based chemical biorefining and bioenergy products. Data were derived from 78 chip samples from the before-mentioned raw materials, the samples being pooled by tree height position from the sample trees of 42 experimental forest stands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition to stilbenes, Scots pine heartwood also contains resin acids, the content of which was not analysed in the present study. The total resin acid content is higher than the stilbene content [10,[27][28][29]. The resin acids are also the main components of pine sapwood and spruce extracts [10,11].…”
Section: Discussionmentioning
confidence: 95%
“…In addition to stilbenes, Scots pine heartwood also contains resin acids, the content of which was not analysed in the present study. The total resin acid content is higher than the stilbene content [10,[27][28][29]. The resin acids are also the main components of pine sapwood and spruce extracts [10,11].…”
Section: Discussionmentioning
confidence: 95%
“…The relative pattern of resin acids in different parts (stem wood, stem wood thinning, sawdust, branch biomass and bark) of P. sylvestris from different climatic regions in Finland has been described by Verkasalo et al. ( 2022 ). Overall, the most abundant compounds were abietic acid (0.404–3.994 mg/g dw) and dehydroabietic acid (0.707–3.290 mg/g dw), followed by neoabietic acid (0–2.868 mg/g dw), levopimaric acid (0.012–2.796 mg/g dw), palustric acid (0–2.707 mg/g dw), pimaric acid (0.373–1.731 mg/g dw), isopimaric acid (0.270–1.135 mg/g dw), sandaracopimaric (0.091–0.307 mg/g dw).…”
Section: Assessmentmentioning
confidence: 94%
“…Several publications reported the presence of resin acids (abietic acid, neoabietic acid, dehydroabietic acid, levopimaric acid, palustric acid, pimaric acid, isopimaric acid, sandaracopimaric acid) in P. sylvestris wood (15-25 mg/g) and needles (about 5 mg/g) (Manninen et al, 2002;Ekeberg et al, 2006;Hovelstad et al, 2006). The relative pattern of resin acids in different parts (stem wood, stem wood thinning, sawdust, branch biomass and bark) of P. sylvestris from different climatic regions in Finland has been described by Verkasalo et al (2022). Overall, the most abundant compounds were abietic acid (0.404-3.994 mg/g dw) and dehydroabietic acid (0.707-3.290 mg/g dw), followed by neoabietic acid (0-2.868 mg/g dw), levopimaric acid (0.012-2.796 mg/g dw), palustric acid (0-2.707 mg/g dw), pimaric acid (0.373-1.731 mg/g dw), isopimaric acid (0.270-1.135 mg/g dw), sandaracopimaric (0.091-0.307 mg/g dw).…”
Section: Substances Of Concernmentioning
confidence: 99%
“…Ewunie et al [32] reported that the extractive components in pretreated Jatropha curcas fruit shell (JCFS) were comparatively lower than the untreated JCFS. The extractives in plant materials consist of lipids, phenolic compounds, terpenoids, fatty acids, resin acids, sterol esters, sterol, and waxes [33]. At relatively lower temperatures (40 • C), the NaOH concentration had more effect on increasing holocellulose content [34].…”
Section: Effect Of Chemical and Steam Explosion Pulping Methods On Th...mentioning
confidence: 99%